Concentrate Inspection Campaign (CIC) Fire Safety di Kapal oleh Biro Klasifikasi RINA - fakhrurrozi, fakhrurrozi (Politeknik Bumi Akpelni, 2023)
Registro Italiano Navale (RINA), as an international classification bureau, 2023 will hold a campaign in every inspection of ships under its classification for fire safety. This campaign is based on data findings from Port State Control (PSC), which over the past 5 (five) years found a lot of deficiencies in fire safety on ships, which are not following the provisions of SOLAS regulations 1974 Chapter II-2 and also the skipper and crew, incompetent in carrying out fire drills, which are not under the fire training scenario on ships. The research method used by the author is a qualitative research approach. Then, data processing is carried out by reviewing the results of the RINA Classification PSC examination, Tokyo MoU, and Paris MoU, which are then examined as secondary data. The discussion in this study examines the discrepancies that become the findings of the PSC, including focusing on emergency escape routes, fire doors, fire detection devices and fire alarm systems, ventilation cover equipment, control facilities for power ventilation in the engine room, fire pumps, fix gas fire fighting systems and fire drills.